2018
DOI: 10.1155/2018/1746391
|View full text |Cite
|
Sign up to set email alerts
|

Host Immunological Effects of Partial Splenic Embolization in Patients with Liver Cirrhosis

Abstract: Purpose Restoration of the balance between T lymphocyte subsets and between Th1/Th2 cytokines together with improvement of antitumor immunity has been reported after hepatosplenectomy in patients with liver cirrhosis (LC) and hepatocellular carcinoma (HCC). However, the detailed effects of partial splenic embolization (PSE) on host immunity are unknown. Accordingly, this study evaluated host immunity in patients with cirrhosis receiving PSE for thrombocytopenia. Methods Twenty-three adult Japanese patients wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 45 publications
0
11
0
Order By: Relevance
“…The immediate improvement in the WBC count due to PSE could be attributed to the release of white cells from the spleen, considering it as an acute inflammatory response. The long-term improvement in the WBC count in the EP group could be ascribed to an improvement in the bloodproducing function of the bone marrow after PSE [26,27].…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…The immediate improvement in the WBC count due to PSE could be attributed to the release of white cells from the spleen, considering it as an acute inflammatory response. The long-term improvement in the WBC count in the EP group could be ascribed to an improvement in the bloodproducing function of the bone marrow after PSE [26,27].…”
Section: Discussionmentioning
confidence: 93%
“…The immediate improvement in the WBC count due to PSE could be attributed to the release of white cells from the spleen, considering it as an acute inflammatory response. The long-term improvement in the WBC count in the EP group could be ascribed to an improvement in the blood-producing function of the bone marrow after PSE [ 26 , 27 ]. The PLT count might have increased due to improvement in the hepatic production of thrombopoietin (TPO) after PSE, as well as due to the reduction in the splenic platelet pool and increase in the platelet survival time [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…PSE can reduce the absolute number of Th2 lymphocytes, restore the Th1/Th2 imbalance, to the advantage of Th1, thereby inhibiting liver fibrosis. [ 26 , 27 ] Also, thrombocytosis after PSE can also inhibit liver fibrosis. [ 28 ] Improved liver function can enhance liver protein synthesis and reduce the severity of hepatic encephalopathy.…”
Section: Discussionmentioning
confidence: 99%
“…Partial splenic embolization (PSE) via catheter intervention is also known to be an effective alternative to splenectomy that is less invasive than surgery. Interestingly, Matsukiyo et al recently reported that PSE not only improve leukopenia and thrombocytopenia but also induce activation of CD4 + T cells, including Th1 and Th2 cells, in patients with cirrhosis and thrombocytopenia (44). Because the current study did not address Th1 and Th2 cytokine expression and their balance in CD4 + T cells, it would be interesting to examine them before and after splenectomy and compare them with those after PSE in cirrhotic patients in future studies.…”
Section: Discussionmentioning
confidence: 87%